Evaluating smog awareness and preventive practices among Pakistani general population: a cross-sectional survey. Issue 3 (4th May 2019) - Saleem, Zikria; Saeed, Hamid; Yousaf, Mahrukh; Asif, Usama; Hashmi, Furqan Khurshid; Salman, Muhammad; Hassali, Mohamed Azmi
ABSTRACT: Smog pollution is one of the serious public health concerns worldwide. This study aimed to evaluate the awareness and preventive practices of smog among general population belonging to one of the industrialized cities (Lahore) of Pakistan. A cross-sectional survey was carried out among 607 individuals using a 46-item self-administered questionnaire. Data was analyzed using SPSS (version 20.0). The overall adequate knowledge was 74% ( n = 449). Majority of individuals having Science qualifications (89.4%) exhibited adequate knowledge of smog as compared to those with Arts qualifications (OR; 4.73, p -value < 0.001). Significant associations were observed between the practice and family income (OR; 1.710, p -value = 0.004), educational group (OR; 1.648, p -value = 0.011), employment status (OR; 0.371, p -value < 0.001) and smoking history (OR; 0.260, p -value < 0.001). Respondents having good family income were following several preventive measures to avoid interaction with smog pollution. Government and environmental health agencies in Pakistan should take steps to improve the awareness and preventive practices of masses particularly of those with non-science qualification and low income to avoid adverse outcomes associated with smog pollution. Abbreviations: CDGL: City District Government of Lahore; WHO: World Health Organization; EPA: Environmental Protection Agency; USA: United States of America; SPSS: Statistical Program for Social Sciences